Georgia Architectural and Historic Properties Survey of Rural [124] Mid west section of the county, Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [124] Mid west section of the county, Quitman, Ga. December 1980. Easter Plantation. A one rectangular plan with hipped tin and shiplap siding. Hipped porch with square posts. Sash windows with 2/2 lights. Interior chimney. Brick piers. Good condition. Date of Construction: Unknown. A typical vernacular farmhouse common to their rural area.
Georgia Architectural and Historic Properties Survey of Rural [124] Mid west section of the county, Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 828 KB (848,755 bytes).
Keywords: Historic Buildings; Historic Properties Survey; Lowndes County Historical Society (Lowndes County, Ga); Brooks County, GA.; Quitman, Ga.